Alteration of blood glucose and hemoglobin levels in zebrafish exposed to sumithion (Progressive Agriculture, 2016)
Sumithion is extensively used in the agricultural land to control brittle and larval rearing aquaculture ponds to control tiger bug. The present study was conducted to evaluate the effects of sumithion on blood glucose and hemoglobin levels in zebrafish, Danio rerio. At first acute toxicity (96 h LC50 value 7.89 mg/L) of sumithion was determined for sexually matured zebrafish. Then the fish were exposed to four concentrations (0, 0.5, 1.0 and 2.0 mg/L) of sumithion for a period of 7 days. The sexual dimorphic changes in blood glucose levels were observed in the present study. In male, the blood glucose levels were significantly (P